Antifungal Activity of the Liquid Obtained by Oxidative Cracking of Waste Paper - Perveenb, Shahnaz; Hussaina, Zahid; Khan, Khalid M. (Biological Sciences - PJSIR, 2008)
. The composition of the product formed by burning of paper under controlled conditions in an indigenously prepared reactor was determined by GC/MS, while its antifungal activity was assessed qualitatively and quantitatively by comparison with the standard and determination of the MIC. The product was found to be effective against six fungal strains. Amount of the product has been improved upto 25%.